Stigmatization, liability and public enforcement of law - Clemens Buchen; Bruno Deffains; Alberto Palermo (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2018)
In the theory of public enforcement of law the choice of the liability rules is between strict liability and fault-based liability. In this paper, we study the determinants of compliance when in addition to standard economic incentives wrongdoers take into account stigmatization costs. In this context, this cost is not simply a transfer of resources. We show that a non-guiltiness standard - the fault standard equal to the deterrence level - is never optimal. In this scenario, we show how the optimal policy choice depends on the interplay between the magnitude of the harm and the stigmatization cost.
Keywords: K13; K42; 330; Stigmatization; Regulatory Offenses; Law Enforcement; Strict Liability; Negligence; Legal Standard; Compliance; Deterrence